A Family Affair: Job Loss and the Mental Health of Spouses and Adolescents - Melisa Bubonya; Deborah A. Cobb-Clark; Mark Wooden (Institute for the Study of Labor (IZA), 2014)
This study examines the impact of involuntary job loss on the mental health of family members. Estimates from fixed-effects panel data models, using panel data for Australia, provide little evidence of any negative spillover effect on the mental health of husbands as a result of their wives' job loss. The mental well-being of wives, however, declines following their husbands' job loss, but only if that job loss results in a sustained period of non-employment or if the couple experienced financial hardship or relationship strain prior to the husband's job loss. A negative effect of parental job loss on the mental health of co-resident adolescent children is also found, but appears to be restricted to girls.
Keywords: I31; J10; J65; 330; unemployment; involuntary job loss; mental health; families; spouses; adolescents; HILDA Survey